Theory of liquid and plastic limits for fine soils, methods of determination and outlook - O'Kelly, Brendan (My University, 2024)
Albert Atterberg introduced various consistency limits (state transitions) for fine-grained soil in the 1910s. Of these, the liquid limit (LL) and plastic limit (PL) are ubiquitous in geotechnical engineering practice, including their usage for soil classification and in deducing useful geotechnical parameters through correlations. Given that it is about 110 years since they were first introduced, it seems timely to review critically the current state of play regarding various definitions and theories of these index parameters and their standardised testing methods, as described in majorly used codes worldwide. Because different codes allow different LL apparatus types and employ some dissimilar criteria (e.g. in establishing the end point for the PL test), a change in method or code may produce different consistency limits results for testing the same soil. These differences are rationalised in terms of the controlling soil and test parameters. Some potential pitfalls in consistency limits testing are highlighted. Attention then turns to strength-based approaches, mostly employing fall-cone (FC) set-ups, emphasising their unsuitability for determining Atterberg’s PL. Considering the general poor reproducibility of the PL test, this paper concludes with an alternative way forward, obtaining useful FC index parameters that provide new possibilities for strength predictions and in the classification of fine-grained soils.
PUBLISHED
Keywords: characterisation techniques/codes of practice & standards/penetrometers/plasticity/soil classification/testing, apparatus & methods; Smart & Sustainable Planet; GEOTECHNICAL ENGINEERING; Geotechnics; Soil Mechanics; Soil Mechanics & Foundations; soil classification